STUDY OF PREPARATION OF FINANCIAL STATEMENTS IN ACCORDANCE IN ACCORDANCE WITH GOVERNMENT REGULATION NUMBER 24 YEAR 2005 ON SAP (Case Study In Solok City Government) - Darmadi, Cherie; Isafaatun, SE., MM, Eliya; ekowati, SE., MM, Dhiana (Accounting, 2009)
To achieve a transparent and accountable governance in accordance with the principles of good governance in the management of state finances, the government issued a three-pack of Law in the financial sector that is the Act No. 17 year 2003 on State Finance, Law No. 1 of 2004 on State Treasury and the Law No. 15 year 2004 concerning the Management Audit and State Financial Responsibility, and the issuance of Law no. 32 of 2004 on Regional Governance and Law No. 33 of 2004 on Financial Balance between Central Government and Local Government which affects the entire system of financial management. Law has been expressly mandated that within the framework of the state financial accountability, financial reports should be presented by the government based on the Government Accounting Standards. Realization of Consolidated Budget and Balance Sheet by the City of Solok during the Year 2005 and 2006 are still based on Kepmendagri No. 29 year 2002, while SAP was implemented in the presentation of Budget Realization Report and Balance Sheet in 2007 and 2008. This demonstrates the Government of the City of Solok not ready to comply with PP. 24 of 2005 that the financial statements shall be prepared and presented by SAP. Form of the Balance Sheet before the appropriate SAP simpler, whereas according to SAP after more detailed description. For example look at the Current Assets, Long-Term Investment, Other Assets, Liabilities Short- Term, Long Term Liabilities and Equity Funds, except for Fixed Assets. But the Budget Realization Report after appropriate SAP more concise than before according to the SAP due to several differences in the classification, eg based revenue source (PAD, Revenue Transfers, and Other Income sah) and expenditure by type of expenditure (Operating Expenditure, Capital Expenditure, Expenditure Profit Sharing and Financial Aid, and Unexpected Expenditures). Solok City´s financial condition can be seen from the growth and contribution of PAD, Revenue Sharing and Other Revenue Authorized to budget. Constraints faced by the Government of theCity of Solok in the SAP implementation of acquisition pricing for fixed assets is still problematic because of insufficient availability of proof of ownership and does not know the exact date of purchase on the old assets of the City Government, the basis for determining the allocation of capital expenditure on each SKPD until now there has been clear, the availability of HR staff accounting educational backgrounds that are still low, and the attention of regional governments more focused on political issues that successful direct elections. Keywords : financial statements, government regulation number 24 year 2005, SAP